Faktor-Faktor Dalam Desain Penunjang Buku Autobiografi I Made Ada - ., Asthararianty; Dektisa H., Andrian; Cahyadi, Jacky (Nirmana, 2009)
A sculptor named I Made Ada that comes from Pakuduwi village, Tegallalang, Gianyar, Bali and his work of garuda statues have been recognized worlwide. His works are spread all over the world. It causes fear that history will be repeated again. That is a claim from our neighboring country about our origins’ culture. The journey of I Made Ada the sculptor is worth to be documented as an autobiography that contains and tells every authentic data in detail and also so that Indonesian people may know about I Made Ada’s existence. The method used to collect all the needed data are observation, interview, and documentation. The making of an autobiography can create an understanding that this is one of Indonesian richness cultures that need to be kept and preserved. Furthermore, this book is presented as an authentic proof that can facilitate in managing patents and legality rights processes on intellectual properties. This autobiography book is designed by combining modern with traditional impressions and supported by photography, information resources, and other attractive interests.